A computer-aided design tool for biomedical OBT sensor tuning in cell-culture assays. (March 2021) - Pérez, P.; Serrano, J.A.; Martín, M.E.; Daza, P.; Huertas, G.; Yúfera, A.
Highlights: A CAD tool for real-time cell culture monitoring system design is developed Generates an equivalent electric circuit for the cell-electrode based on area cell dynamics Proposes an Oscillation Based Test (OBT) parameterized circuit for cell culture bioimpedance test Simulates electrically the full system to define the best system parameter sensor values Experimental results are reported with commercial gold electrodes and the AA8 cell line Abstract: Background and objectives: The biomedical engineering must frequently develop sensor designs by including information from performance of bio-samples (cell cultures or tissues), technical specifications of transducers, and constrains from electronic circuits. A computer program for real-time cell culture monitoring system design is developed; analyzing, modelling and integrating into the program design flow the electrodes, cell culture and test circuit's influences. Methods: The computer tool, first, generates an equivalent electric circuit model for the cell-electrode bio-systems based on the area covered by cells, which also considers the cell culture dynamics. Second, proposes an Oscillation Based Test (OBT) parameterized circuit, for Electrical Cell-Substrate Sensing (ECIS) measurements of the cell culture system bioimpedance. Third, simulates electrically the full system to define the best system parameter values for the sensor. Results: Reported experimental results are based on commercial gold electrodes and the AA8 cell line. Characteristics of the cell lines, as time-division or cell size, are incorporated into the program design flow, showing that for a given assay, the optimal OBT circuit parameters can be selected with the help of the computer tool. The electrical simulations of the full system demonstrate that the can be correctly predicted the output frequency and amplitude ranges of the voltage response, obtaining accurate results when cell culture approaches to confluence phase. Conclusion: It is proposed a computer program for system design of biosensors applied to monitoring cell culture dynamics. The program allows obtaining confident system information by electrical stimulation. All system components (electrodes, cell culture and test circuits) are properly modelled. The employed procedure can be applied to any other 2D electrode layout or alternative circuit technique for ECIS test. Finally, deep insight information on cell size, number, and time-division can be extracted from the comparison with real cell culture assays in the future.